Nano silicon-graphene-bacterial cellulose composite aerogel and preparation method thereof
By introducing nanosilicon into graphene-bacterial cellulose composite aerogel and using membrane-liquid interface culture technology, the problems of poor lithium storage performance and small capacity in the existing technology are solved, and the preparation of nanosilicon-graphene-bacterial cellulose composite aerogel with high capacity and good circulation performance is achieved.
Patent Information
- Application Number
- CN202311309131.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-11
AI Technical Summary
The existing graphene-silica composite aerogels do not have lithium storage properties. Graphene aerogels loaded with silicon nanoparticles have small content of primary silicon and are prone to agglomeration, resulting in a small capacity and cannot meet the needs of high capacity and good cycle performance.
The preparation method of nanosilicon-graphene-bacterial cellulose composite aerogel was used, and a simple and pollution-free aerogel with uniform silicon particle distribution was prepared through membrane-liquid interface culture technology, using bacterial cellulose scaffolds and nanosilicon and graphene as reinforcement materials.
The uniform distribution of silicon particles inside the aerogel is achieved, the specific capacity, reversible capacity and cycling performance are improved, suitable for large-scale production, and the preparation cost is reduced.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical batteries, and in particular to a nano silicon-graphene-bacterial cellulose composite aerogel and a preparation method thereof. Background Art
[0002] With the improvement of science and technology, people's demand for energy is increasing. People convert renewable energy such as solar energy, wind energy, nuclear energy and biomass energy into electricity for production and life, and the storage of electricity has also evolved into a new problem. The development of secondary batteries with high charge and discharge capacity, fast cycle rate, long-term use and low cost is an effective way to achieve sustainable development. At present, most secondary batteries on the market are lithium-ion batteries, but the capacity of commercial graphite electrodes is only 376 mAh / g, which is difficult to meet the high capacity demand of electric vehicles and hybrid electric vehicles. Silicon-based negative electrode materials have attracted widespread attention due to their high lithium insertion capacity. At the same time, silicon is one of the most abundant elements in the earth's crust, with low price and environmental friendliness. Therefore, silicon is expected to replace graphite as a negative electrode material. However, silicon will undergo a huge volume change (300%) during the process of lithium insertion and extraction, resulting in the pulverization and fragmentation of silicon particles, and the loss of electrical contact between silicon particles and between silicon particles and current collectors, which in turn causes the initial capacity to decay exponentially and the cycle reversibility is very low. Studies have shown that materials with stable porous structures can provide effective space for their huge volume expansion, and aerogel is the most ideal material. Existing graphene-silicon dioxide composite aerogels do not have lithium storage properties, and graphene aerogels loaded with silicon nanoparticles also have a small capacity due to the low content of active substance elemental silicon and easy agglomeration. Summary of the invention
[0003] The purpose of the present invention is to provide a nano-silicon-graphene-bacterial cellulose composite aerogel and a preparation method, so that the silicon particles inside the aerogel are evenly distributed, the preparation process is simple, pollution-free, and suitable for large-scale production. The aerogel prepared by the method of the present invention has the characteristics of high specific capacity, large reversible capacity and good cycle performance.
[0004] In order to achieve the above-mentioned object of the invention, the technical solution adopted by the present invention is as follows: A method for preparing nano-silicon-graphene-bacterial cellulose composite aerogel comprises the following steps: Step 1: Prepare bacterial cellulose culture medium and place it in an autoclave for sterilization at 115 °C and 0.1 MPa for 30 min; Step 2: Prepare mixed culture medium: Preparation of modified nano-silicon: First, add 3 g of diethylene glycol phthalate diacrylate and 600 mg of nano-silicon to 120 mL of distilled water in sequence and stir until completely decomposed; then centrifuge and dry to obtain modified nano-silicon, and sterilize with ultraviolet light; Preparation of nano-silicon / graphene dispersion: Deionized water was used to prepare a nano-silicon / graphene dispersion with a mass volume ratio of 1 mg / mL, ultrasonicated for 30 min, and sterilized with UV light; Take an appropriate amount of nano-silicon / graphene dispersion and add it to an appropriate uninoculated culture medium at a volume ratio of 1:1 to 40, and ultrasonicate for 30 min to evenly disperse the nano-silicon and graphene in the culture medium; Step 3: Inoculate the bacteria into the culture medium under a sterile condition and culture it in a constant temperature incubator (temperature is 30 °C) for 24 to 72 hours to obtain a base membrane with a thickness of 1 to 2 mm as a membrane liquid interface for culturing nano-silicon-graphene-bacterial cellulose composite aerogel; Step 4: Spray the mixed culture medium of different concentrations of nano-silicon / graphene prepared in step 5 on the basement membrane described in step 3 in the form of mist, spray 10 to 200 times, wait for the mixed culture medium on the membrane surface to be completely consumed after each spraying before spraying again, and finally obtain a nano-silicon / graphene / bacterial cellulose composite membrane with a thickness of 1 to 50 mm, wash it with clean water, freeze-dry it, and store it; Step 5: Place the freeze-dried sample from step 4 in a reactor, introduce inert gas and heat the reaction to 600-1000 °C for 1-2 h, cool the reactor to room temperature, and take out the carbonized sample, which is the nano-silicon-graphene-bacterial cellulose composite aerogel.
[0005] Compared with the prior art, the present invention has the following beneficial effects: The method of the present invention uses bacterial cellulose scaffold as a skeleton, silicon nanoparticles and graphene as reinforcing materials, and the prepared nano silicon-graphene-bacterial cellulose composite aerogel is used as the negative electrode material of the lithium ion battery. On the one hand, the unique three-dimensional and porous structure of the nano silicon-graphene-bacterial cellulose composite aerogel and the structural strength of the nano silicon / graphene reinforced aerogel can inhibit the agglomeration of silicon nanoparticles and the volume change of silicon during the lithium insertion and extraction process, thereby improving the conductivity of the negative electrode material; on the other hand, it improves the reaction kinetics of the carbon pole, provides more active sites for energy storage during the charge and discharge process, and gives play to the electrochemical advantages of the active substance silicon. Each component in the composite aerogel of the present invention gives full play to its own advantages and makes up for each other's defects, thereby obtaining an electrode material with excellent electrochemical performance.
[0006] The method for preparing the nano-silicon-graphene-bacterial cellulose composite aerogel proposed in the present invention does not use any toxic chemical reagents in the entire process, the process is simple and controllable, the preparation cost is low, it is environmentally friendly and pollution-free, and the prepared aerogel improves its overall electrochemical performance to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1This is a macroscopic photograph of the nano-silicon-graphene-bacterial cellulose composite aerogel prepared in Example 1.
[0008] Figure 2 This is a macroscopic photograph of the nano-silicon-graphene-bacterial cellulose composite aerogel prepared in Example 1.
[0009] Figure 3 This is a macroscopic photograph of the nano-silicon-graphene-bacterial cellulose composite aerogel prepared in Example 1.
[0010] Figure 4 This is the SEM photo of the nano-silicon-graphene-bacterial cellulose composite aerogel prepared in Example 1.
[0011] Figure 5 This is the SEM photo of the nano-silicon-graphene-bacterial cellulose composite aerogel prepared in Example 2.
[0012] Figure 6 This is the SEM photo of the nano-silicon-graphene-bacterial cellulose composite aerogel prepared in Example 3. Implementation
[0013] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The embodiments are provided for a better understanding of the present invention and are by no means intended to limit the present invention.
[0014] The nano-silicon-graphene-bacterial cellulose composite aerogel proposed in the present invention is composed of nano-silicon, graphene and bacterial cellulose. The membrane-liquid interface culture technology is adopted. First, the bacterial cellulose basement membrane is obtained by static culture method, and then the culture solution containing nano-silicon and graphene at different concentrations is sprayed on the basement membrane for many times to achieve membrane-liquid contact, thereby obtaining the nano-silicon-graphene-bacterial cellulose composite aerogel. The preparation process is simple, no toxic chemical reagents are used, the preparation cost is low, and the environment is friendly and pollution-free.
[0015] Example 1: Nano-silicon, graphene and bacterial cellulose were used as raw materials and membrane-liquid interface culture technology was used to prepare nano-silicon-graphene-bacterial cellulose composite aerogel. The specific steps are as follows: Step 1: Prepare the culture medium: first weigh 5 g of disodium hydrogen phosphate, 25 g of glucose, 10 g of peptone, and 7.5 g of yeast powder, and then add them to a beaker containing 1000 mL of deionized water in sequence, and stir until they are completely dissolved; adjust the pH value of the system to between 4 and 5 with glacial acetic acid to prepare the culture medium, and place it in an autoclave, sterilize it at 115 °C and 0.1 MPa for 30 min, and obtain the uninoculated culture medium for later use; Step 2: Prepare three mixed culture media with different volume ratios: Preparation of modified nano-silicon: First, add 3 g of diethylene glycol phthalate diacrylate and 600 mg of nano-silicon to 120 mL of distilled water in sequence and stir until completely decomposed; then centrifuge and dry to obtain modified nano-silicon, and sterilize with ultraviolet light; Preparation of nano-silicon / graphene dispersion: Deionized water was used to prepare a nano-silicon / graphene dispersion with a mass volume ratio of 1 mg / mL, ultrasonicated for 30 min, and sterilized with UV light; Take an appropriate amount of nano-silicon / graphene dispersion and add it to an appropriate uninoculated culture medium at a volume ratio of 1:10, and ultrasonicate for 30 min to evenly disperse the nano-silicon and graphene in the culture medium; Step 3: Inoculate the bacteria into the culture medium under a sterile condition and culture it in a constant temperature incubator (temperature is 30 °C) for 24 to 72 hours to obtain a base membrane with a thickness of 1 to 2 mm as a membrane liquid interface for culturing nano-silicon-graphene-bacterial cellulose composite aerogel; Step 4: Spray the mixed culture medium of different concentrations of nano-silicon / graphene prepared in step 3 on the basement membrane described in step 2 in the form of mist, spray 10 to 200 times, wait for the mixed culture medium on the membrane surface to be completely consumed after each spraying before spraying again, and finally obtain a nano-silicon / graphene / bacterial cellulose composite membrane with a thickness of 1 to 50 mm, wash it with clean water, freeze-dry it, and then store it; Step 5: Place the freeze-dried sample from step 4 in a reactor, introduce inert gas and heat the reaction to 600-1000 °C for 1-2 h, cool the reactor to room temperature, and take out the carbonized sample, which is the nano-silicon-graphene-bacterial cellulose composite aerogel.
[0016] Example 2: Nano-silicon, graphene and bacterial cellulose were used as raw materials and membrane-liquid interface culture technology was used to prepare nano-silicon-graphene-bacterial cellulose composite aerogel. The specific steps are as follows: Step 1: Prepare the culture medium: first weigh 5 g of disodium hydrogen phosphate, 25 g of glucose, 10 g of peptone, and 7.5 g of yeast powder, and then add them to a beaker containing 1000 mL of deionized water in sequence, and stir until they are completely dissolved; adjust the pH value of the system to between 4 and 5 with glacial acetic acid to prepare the culture medium, and place it in an autoclave, sterilize it at 115 °C and 0.1 MPa for 30 min, and obtain the uninoculated culture medium for later use; Step 2: Prepare three mixed culture media with different volume ratios: Preparation of modified nano-silicon: First, add 3 g of diethylene glycol phthalate diacrylate and 600 mg of nano-silicon to 120 mL of distilled water in sequence and stir until completely decomposed; then centrifuge and dry to obtain modified nano-silicon, and sterilize with ultraviolet light; Preparation of nano-silicon / graphene dispersion: Deionized water was used to prepare a nano-silicon / graphene dispersion with a mass volume ratio of 1 mg / mL, ultrasonicated for 30 min, and sterilized with UV light; Take an appropriate amount of nano-silicon / graphene dispersion and add it to an appropriate uninoculated culture medium at a volume ratio of 1:20, and ultrasonicate for 30 min to evenly disperse the nano-silicon and graphene in the culture medium; Step 3: Inoculate the bacteria into the culture medium under a sterile condition and culture it in a constant temperature incubator (temperature is 30 °C) for 24 to 72 hours to obtain a base membrane with a thickness of 1 to 2 mm as a membrane liquid interface for culturing nano-silicon-graphene-bacterial cellulose composite aerogel; Step 4: Spray the mixed culture medium of different concentrations of nano-silicon / graphene prepared in step 3 on the basement membrane described in step 2 in the form of mist, spray 10 to 200 times, wait for the mixed culture medium on the membrane surface to be completely consumed after each spraying before spraying again, and finally obtain a nano-silicon / graphene / bacterial cellulose composite membrane with a thickness of 1 to 50 mm, wash it with clean water, freeze-dry it, and then store it; Step 5: Place the freeze-dried sample from step 4 in a reactor, introduce inert gas and heat the reaction to 600-1000 °C for 1-2 h, cool the reactor to room temperature, and take out the carbonized sample, which is the nano-silicon-graphene-bacterial cellulose composite aerogel.
[0017] Example 3: Nano-silicon, graphene and bacterial cellulose were used as raw materials and membrane-liquid interface culture technology was used to prepare nano-silicon-graphene-bacterial cellulose composite aerogel. The specific steps are as follows: Step 1: Prepare the culture medium: first weigh 5 g of disodium hydrogen phosphate, 25 g of glucose, 10 g of peptone, and 7.5 g of yeast powder, and then add them to a beaker containing 1000 mL of deionized water in sequence, and stir until they are completely dissolved; adjust the pH value of the system to between 4 and 5 with glacial acetic acid to prepare the culture medium, and place it in an autoclave, sterilize it at 115 °C and 0.1 MPa for 30 min, and obtain the uninoculated culture medium for later use; Step 2: Prepare three mixed culture media with different volume ratios: Preparation of modified nano-silicon: First, add 3 g of diethylene glycol phthalate diacrylate and 600 mg of nano-silicon to 120 mL of distilled water in sequence and stir until completely decomposed; then centrifuge and dry to obtain modified nano-silicon, and sterilize with ultraviolet light; Preparation of nano-silicon / graphene dispersion: Deionized water was used to prepare a nano-silicon / graphene dispersion with a mass volume ratio of 1 mg / mL, ultrasonicated for 30 min, and sterilized with UV light; Take an appropriate amount of nano-silicon / graphene dispersion and add it to an appropriate uninoculated culture medium at a volume ratio of 1:30, and ultrasonicate for 30 min to evenly disperse the nano-silicon and graphene in the culture medium; Step 3: Inoculate the bacteria into the culture medium under a sterile condition and culture it in a constant temperature incubator (temperature is 30 °C) for 24 to 72 hours to obtain a base membrane with a thickness of 1 to 2 mm as a membrane liquid interface for culturing nano-silicon-graphene-bacterial cellulose composite aerogel; Step 4: Spray the mixed culture medium of different concentrations of nano-silicon / graphene prepared in step 3 on the basement membrane described in step 2 in the form of mist, spray 10 to 200 times, wait for the mixed culture medium on the membrane surface to be completely consumed after each spraying before spraying again, and finally obtain a nano-silicon / graphene / bacterial cellulose composite membrane with a thickness of 1 to 50 mm, wash it with clean water, freeze-dry it, and then store it; Step 5: Place the freeze-dried sample from step 4 in a reactor, introduce inert gas and heat the reaction to 600-1000 °C for 1-2 h, cool the reactor to room temperature, and take out the carbonized sample, which is the nano-silicon-graphene-bacterial cellulose composite aerogel.
Claims
1. A nano-silicon-graphene-bacterial cellulose composite aerogel, wherein the composite material is composed of nano-silicon, graphene and bacterial cellulose, characterized in that: The membrane-liquid interface culture technology was used to spray 10 to 200 times a mixed culture medium containing nano-silicon / graphene with a mass volume concentration of 0.023 to 0.33 mg / mL on the surface of the bacterial cellulose-based membrane prepared by the traditional static culture technology to achieve membrane-liquid interface contact for culture, and finally prepare nano-silicon-graphene-bacterial cellulose composite aerogel; the specific steps are as follows: Step 1: Prepare bacterial cellulose culture medium and place it in an autoclave for sterilization at 115 °C and 0.1 MPa for 30 min; Step 2: Prepare mixed culture medium: Preparation of modified nano-silicon: First, add 3 g of diethylene glycol phthalate diacrylate and 600 mg of nano-silicon to 120 mL of distilled water in sequence and stir until completely decomposed; then centrifuge and dry to obtain modified nano-silicon, and sterilize with ultraviolet light; Preparation of nano-silicon / graphene dispersion: Deionized water was used to prepare a nano-silicon / graphene dispersion with a mass volume ratio of 1 mg / mL, ultrasonicated for 30 min, and sterilized with UV light; Take an appropriate amount of nano-silicon / graphene dispersion and add it to an appropriate uninoculated culture medium at a volume ratio of 1: 1-40, and ultrasonicate for 30 min to evenly disperse the nano-silicon and graphene in the culture medium; Step 3: Inoculate the bacteria into the culture medium under a sterile condition and culture it in a constant temperature incubator (temperature is 30 °C) for 24 to 72 hours to obtain a base membrane with a thickness of 1 to 2 mm as a membrane liquid interface for culturing nano-silicon-graphene-bacterial cellulose composite aerogel; Step 4: Spray the mixed culture medium of different concentrations of nano-silicon / graphene prepared in step 3 on the basement membrane described in step 3 in the form of mist, spray 10 to 200 times, wait for the mixed culture medium on the membrane surface to be completely consumed after each spraying before spraying again, and finally obtain a nano-silicon / graphene / bacterial cellulose composite membrane with a thickness of 1 to 50 mm, wash it with clean water, freeze-dry it, and then store it; Step 5: Place the freeze-dried sample from step 4 in a reactor, introduce inert gas and heat the reaction to 600-1000 °C for 1-2 h, cool the reactor to room temperature, and take out the carbonized sample, which is the nano-silicon-graphene-bacterial cellulose composite aerogel.
2. The method for preparing the nano-silicon-graphene-bacterial cellulose composite aerogel according to claim 1, characterized in that: The graphene includes one of graphene oxide, MXene, red phosphorene, germanene and carbon nanotube.
3. The method for preparing the nano-silicon-graphene-bacterial cellulose composite aerogel according to claim 1, characterized in that: The modifier includes one or more of diethylene glycol phthalate diacrylate and its derivatives.
4. The method for preparing the nano-silicon-graphene-bacterial cellulose composite aerogel according to claim 1, characterized in that: In step 2, the graphene and nano-silicon contents of the graphene dispersion are both 0.5-2 mg / mL.